PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PENYELEKSIAN NASKAH LAYAK MENGGUNAKAN METODE FAHP - Ekastini Ekastini; Kusrini Kusrini; Emha T aufiq Luthfie (Informasi Interaktif, 2017)
Script selection process is a process for the assessment of the manuscript for eligible published. The assessment conducted by the script editor. The Editor  task of providing evaluation on every script based on criteria and assessment subkriteria. By using the decision support system will facilitate policy makers in determining the eligibility of the script. On this research will be done against the design of decision support system to select the paper worthy of publication that can provide recommendations for policy makers in determining the feasibility of a manuscript for publication or not. Design of decision support system use encryption methods Multi Criteria Decision Making (MCDM). Multi Criteria Decision Making is a method of decision making to determine the best alternative based on a few certain criteria. Keyword: Decision Support System, Script selection, Multi Criteria Decision Making